Winston L. Y. Yang, Peter Li, y Nathan K. Mao. Classical Chinese Fiction; A Guide to Its Study and Appreciation. Boston: G.K. Hall & Co., 1978. pp. XXVI 302. - Maeth Ch., Russell (Estudios de Asia y África, 1981)
-